Faraday rotation based optical fiber components - Zhang, Ansen (2010)
Small sized optical fiber is the key components in many optical systems as it can protect laser sources from disturbing of reflected rays. In order to reduce the insertion loss of optical isolator, different alignment methods are implemented to reducing the coupling loss and hence the insertion loss of the isolator. With the purpose of studying the relationship of insertion loss and structural misalignment, simulations are implemented for analysis. By analyzing the numerical results generated from simulation, factors causing optical losses to isolators can be easily figured out. Hence the requirements for conducting the structure of small sized optical isolator can be deduced more specifically and clearly. The size of the raw materials used to construct the optical isolator is fixed. In order to make them work properly, other necessary components like grooves need to be designed with precise manufacture. Design and construction of optical isolator are implemented with different ways. However, due to the equipment limitations the resultant optical isolator is not as good as expected.